Percutaneous‐endoscopic rendezvous cholangiography with biliary stent placement in a dog with extra‐hepatic biliary duct obstruction. (17th October 2021) - Work, M.; Allerton, F.; Griffin, S.; Kent, A.
Abstract : A middle‐aged male springer spaniel was presented for investigation of acute vomiting, lethargy and icterus. Marked distension of the gall bladder and common bile duct was evident at ultrasound due to obstruction by mineralised intraluminal material. After 48 hours of hospitalisation with intravenous fluid therapy, analgesia and antimicrobial therapy, intervention was deemed necessary to relieve the obstruction. A percutaneous‐endoscopic rendezvous approach was used to achieve placement of a pigtail stent into the distal common bile duct, successfully relieving the obstruction. Serial biochemistry measurements postprocedure confirmed marked improvements in serum bilirubin. The patient remains clinically well 24 months postprocedure, and all hepatic enzyme activities have normalised. Based on the literature search performed, this is the first successful application of this technique in the management of canine extrahepatic biliary duct obstruction.